Measuring the Efficiency of Parallel Discrete Event Simulation in Heterogeneous Execution Environments - Lencse, G.; Derka, I. (Acta Technica Jaurinensis, 2016)
This paper deals with the experimental testing and verification of the earlier proposed load balancing and coupling factor criteria for the conservative parallel discrete event simulation in heterogeneous execution environments whether they can ensure a good speedup. The definition of the relative speedup is extended to the heterogeneous systems in a natural way. This definition is used to measure the efficiency of the parallel simulation executed by heterogeneous systems. A closed queueing network is used as the simulation model. It is demonstrated on the example of a heterogeneous system containing 134 CPU cores of 6 different types of computers that a good speedup can be achieved using the load balancing and coupling factor criteria. It is shown that the extension of the definition of the relative speedup to the heterogeneous systems made it easy to judge the speedup of parallel discrete event simulation in heterogeneous execution environments.